The soviet p.lanned economy - K.N plotnikov (MOSCOW : p.ROGRESS p.UBLISHERS, 1974)
the conversion of backward tsarist Russia into an advanced socialist industriel state the contry of the first atomic electric p.ower stations sp.utniks and sp.acesship.s has been named the soviet miracle in the west . The p.resent volume written by well- known Soviet economists traces the sources of this miracle and p.resents in a p.op.ular from questions of the theory p.lanning and guidance of the soviet econnomy its p.resent and future the book abounds in facts illustrating theoretical p.rop.ositions and offers relevant systematised data
Keywords: soviet p.lanned economy